Superlattice-like SnSb4/Ge thin films for ultra-high speed phase change memory applications. Issue 7 (27th January 2016) - He, Zifang; Wu, Pengzhi; Liu, Ruirui; Zhai, Jiwei; Lai, Tianshu; Song, Sannian; Song, Zhitang
Abstract : Superlattice-like (SLL) SnSb4 /Ge thin films were studied by thermal, electrical and optical methods. Abstract : Superlattice-like (SLL) SnSb4 /Ge thin films were studied by thermal, electrical and optical methods. It was found that SnSb4 (SS) films composited with Ge in a superlattice-like configuration showed better thermal stability. With composited Ge, the temperature of 10-year data retention increased from 54 °C to 139 °C. In the electrical studies, reversible transition of a phase change memory cell based on [SS (8 nm)/Ge (4 nm)]4 could be achieved by using an electrical pulse as short as 500 ns. Moreover, ultrafast crystallization (∼6.54 ns at a energy density of ∼4.47 mJ cm −2 ) in the [SS (8 nm)/Ge (4 nm)]4 film was confirmed, which was essential to achieve rapid data recording in phase change memory.